Pertumbuhan dan Hasil Microgreens Wheatgress Akibat Interval Waktu Pemberian Pupuk Organik Cair Limbah Cair Tahu dan Daun Gamal - Lussy, Nova Deviyanti; Walunguru, Lena; Kabora, Anjelina; Mooy, Lehhy Marlina (Jurnal Agroekoteknologi Tropika Lembab, 2024)
This study aims to determine the effect and obtain the best time interval for applying liquid organic fertilizer (LOF) made from tofu liquid waste and gamal leaves to the growth and yield of wheatgrass microgreens. The research method used a complete randomized design (CRD) with six treatments and four repeats. Treatment consists of: control; LOF time interval for applying 1; 2; 3; 4; and once every 5 days. The results showed that LOF made from tofu liquid waste and gamal leaves at several intervals for applying had a significant effect on the coarseness of growth and the percentage of seed growing power, fresh weight of plants, dry weight of plants, and vitamin C levels, but had no significant effect on total leaf chlorophyll. LOF given at intervals of 3 days is the best time because it produces microgreens wheatgrass with a seed growth density of 93,50%, a percentage of seed growing power 99,50%, a fresh weight of the plant 18,75 g, a dry weight of of the plant 2,42 g, and vitamin C levels of 0,83 mg.